Case Study: Evaluation and Reuse of Rainwater in a Prison in Santa Catarina State, Brazil - João, Jair Juarez; Henckmaier, Matheus Frederico Ferreira; Rosa, Gustavo Reche Santa; Lima, Amanda Schueng; Saciloto, Vitória de Godoy (Journal of Agricultural Studies, 2022)
The capture and reuse of rainwater is a viable alternative in regions where water is scarce or in places where water consumption is high. However, the economic viability of the implementation of an appropriate system is reduced by the need to install pumps, filter pipes and filters. This case study was focused on evaluating the potential for the harvesting and reuse of rainwater in a prison in Santa Catarina State, Brazil. The experiment was carried out at Tubarão prison, where three sampling points were strategically selected for the collection of rainwater. The total area of the prison is 4793.73 m² and in this research only the roof areas of the buildings used to keep inmates in closed and semi-open regimes were used. In total, 3483.53 m² were considered, which guarantees an annual capture of 4314 m3 of water and corresponds to 17% of the water consumed in the prison, providing potential savings of US 5408 per year. After collection, the water was filtered through an activated carbon filter to be applied as reuse water. The results demonstrate significant reductions for all parameters analyzed. In general, the average efficiency was above 70%. The best results were obtained for the removal of suspended solids (94%), dissolved solids (94%), total solids (83) and phosphorus (81%). In addition, removal values for color, chlorides and nitrate were around 70%, verifying that the filtration system with activated carbon is efficient for harvested rainwater.